2017
DOI: 10.1039/c7ta06339c
|View full text |Cite
|
Sign up to set email alerts
|

Unlocking the structure of mixed amorphous-crystalline ceramic oxide films synthesized under low temperature electromagnetic excitation

Abstract: The effect of electromagnetic fields on nanoscale atomic structure was determined using synchrotron X-ray pair distribution function (PDF) analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 72 publications
0
28
0
Order By: Relevance
“…This approach is called 'small box modeling', and it has an obvious benefit of having only a few parameters rather than hundreds, otherwise needed for amorphous materials. This strategy is often used in X-ray and neutron PDF refinement (Petkov et al, 1999;Nakamura et al, 2017;Transue et al, 2019), and will certainly be efficient for ePDF analysis.…”
Section: Reverse Monte Carlo (Rmc)mentioning
confidence: 99%
“…This approach is called 'small box modeling', and it has an obvious benefit of having only a few parameters rather than hundreds, otherwise needed for amorphous materials. This strategy is often used in X-ray and neutron PDF refinement (Petkov et al, 1999;Nakamura et al, 2017;Transue et al, 2019), and will certainly be efficient for ePDF analysis.…”
Section: Reverse Monte Carlo (Rmc)mentioning
confidence: 99%
“…Two such recent reports will be reviewed in this section, covering MWRassisted synthesis of TiNiSn and TiCoSb half-Heusler compounds 33 and titanium dioxide (TiO 2 ) thin films. 5 Birkel et al used a domestic microwave oven (LG Goldstar, Seoul, South Korea) operating at 700 W to synthesize TiNiSn and TiCoSb half-Heusler compounds at significantly reduced reaction times. 33 The reaction time was reduced from more than a week (conventional) to 1 min (microwave).…”
Section: Ex Situ Synchrotron X-ray Studies Of Mwr-assisted Synthmentioning
confidence: 99%
“…By using synchrotron X-ray pair distribution function (PDF) analysis, our work (Nakamura et al), also reported differences in phase composition relative to conventional processes in TiO 2 films synthesized by MWR-assisted synthesis. 5 Unlike XRD, which uses Bragg reflections and characterizes only long-range atomic order (crystalline phases), PDF analysis is capable of quantitatively characterizing both local and long-range atomic order, thus giving information on crystalline and amorphous or locally disordered components in the material. 34 By incorporating both Bragg and diffuse scattering information, PDF analysis provides a powerful new tool to study deviations from the symmetry (e.g., changes in shortrange atomic ordering) that is frequently observed when external fields like MWR are applied.…”
Section: Ex Situ Synchrotron X-ray Studies Of Mwr-assisted Synthmentioning
confidence: 99%
See 2 more Smart Citations